Pembelajaran Menulis Teks Puisi Menggunakan Pendekatan Contextual Teaching and Learning (CTL) Berbantuan Media Visual pada Siswa Kelas X di SMK Taruna Harapan 1 Cipatat - hilda nailil haq (IKIP Siliwangi, 2020)
The background of this research is due to the lack of interest and motivation of students in writing, especially writing poetry texts. Students have difficulty in developing ideas and ideas into written form. In addition, the approach or method used by the teacher is less attractive and effective. The objectives of this research are: 1) To determine the effectiveness in implementing learning to write poetry texts using the CTL approach assisted by visual media; 2) To determine the response of teachers and students to learning to write poetry texts; 3) To find out the difficulties experienced by students in completing the task of writing poetry texts. The method used is descriptive qualitative with a research sample of class X students of SMK Taruna Harapan 1 Cipatat. Learning to write poetry texts using the CTL approach assisted by visual media, went well. The scenario and implementation are appropriate. Teacher and student response to learning is very good. The lowest difficulty knowledge result is 10 ≤ 100 about expressions. Meanwhile, the lowest average skill score is 62 ≤ 100 about language content. Of the 36, there were 29 students who scored above the KKM standard ≥ 75 with a percentage of learning outcomes of 94% in the category of